Peningkatan Produktivitas Ternak Melalui Teknologi Pengolahan Pakan Komplit Fermentasi di Loka Perakitan dan Pengujian Ruminansia Kecil - Randi Mulianda; Rita Rosmala Dewi; Karina Mia Berutu; Octanina Sari Br Sijabat; Alfath Rusdhi; Zul Azmi (Universitas Muhammadiyah Mataram, 2025)
Abstract: The training activity entitled “Improving Livestock Productivity Through Complete Fermented Feed Technology” was conducted at the Local Assembly and Testing Station for Small Ruminants in Sei Putih Village, Galang Subdistrict, Deli Serdang Regency. The objective of this activity was to enhance the knowledge and skills of livestock farmers in processing complete fermented feed as an effective and economical alternative. The training was attended by 24 participants, and evaluation was carried out using pre-test and post-test assessments to measure the improvement in understanding. The results showed an increase in the average score from 42 before the training to 86 afterward, indicating the effectiveness of the program in enhancing participants’ knowledge. These findings suggest that the training contributed to the adoption of fermented feed technology and the dissemination of sustainable, locally-based innovations among smallholder livestock farmers.Abstrak: Kegiatan pelatihan bertajuk “Peningkatan Produktivitas Ternak Melalui Teknologi Pengolahan Pakan Komplit Fermentasi” dilaksanakan di Loka Perakitan dan Pengujian Ruminansia Kecil, Desa Sei Putih, Kecamatan Galang, Kabupaten Deli Serdang. Tujuan kegiatan ini adalah untuk meningkatkan pengetahuan dan keterampilan peternak dalam mengolah pakan komplit fermentasi sebagai alternatif pakan yang efektif dan ekonomis. Pelatihan diikuti oleh 24 peserta, dan evaluasi dilakukan menggunakan pre-test dan post-test untuk menilai peningkatan pemahaman. Hasil evaluasi menunjukkan adanya peningkatan nilai rata-rata dari 42 sebelum pelatihan menjadi 86 setelah pelatihan, yang menunjukkan efektivitas pelatihan dalam meningkatkan pengetahuan peserta. Temuan ini mengindikasikan bahwa pelatihan berkontribusi pada peningkatan adopsi teknologi pakan fermentasi serta penyebaran inovasi lokal yang berkelanjutan di kalangan peternak rakyat.